Extended Pterional Approach for Medial Sphenoid Wing Meningioma: A Series of 47 Patients - Lynch, Jose Carlos (J Neurol Surg B Skull Base, 2020)
Background  To describe our operative strategy and analyze its safety and effectiveness for the removal of medial sphenoid wing meningiomas (MSWMs) through the extended pterional approach. Method  We identified 47 patients with MSWMs who were operated using this approach between 1986 and 2016. Medical charts, operative reports, imaging results, and clinical follow-up evaluations were reviewed and retrospectively analyzed. Results  No surgical mortality was observed in this sample. Gross total resection was achieved in 30 (63.8%) patients. Intradural clinoidectomy was performed in 16 (34%) patients. The median length of follow-up was 8.5 years (range, 1–30 years). Conclusion  The extended pterional approach associated with microsurgery techniques provided excellent results for the removal of MSWMs.